The synthesis of some β-lactams and investigation of their metal-chelating activity, carbonic anhydrase and acetylcholinesterase inhibition profiles. (1st November 2016) - Turan, Burhanettin; Şendil, Kivilcim; Şengül, Emin; Gültekin, Mehmet Serdar; Taslimi, Parham; Gulçin, İlhami and Supuran, Claudiu T.
Abstract: β-Lactam antibiotics are a broad class of antibiotics, consisting of all antibiotic agents that contain a β-lactam ring in their molecular structures. Synthesis of β-lactam analogs, which are containing dichloride atoms and N -methyl, N -aromatic rings, was achieved by Schiff bases and dichloroketene compounds. All the synthesized imines and β-lactam analogs were tested against two physiologically relevant carbonic anhydrase isozymes (hCA I and II) and acetylcholinesterase (AChE). They demponstrated effective inhibitory profiles with K i values in ranging of 3.22-11.18 nM against hCA I, 3.74-10.41 nM against hCA II, and 0.50-1.57 nM against AChE. On the other hand, acetazolamide and dorzolamide clinically used as CA inhibitors, showed K i value of 170.34 and 129.26 nM against hCA I, and 115.43 and 135.67 nM against hCA II, respectively. Also, tacrine used as standard AChE inhibitor showed K i value of 5.70 nM against AChE.